Study on filament width of type-I ELM in EAST using VUV imaging system and simulation. (1st December 2022) - Ming, T.F.; Tang, T.F.; Shi, Q.Q.; Long, F.F.; Hou, S.W.; Deng, R.J.; Xia, T.Y.; Zhang, X.X.; Lian, H.; Wu, X.H.; Fan, H.C.; Li, B.; et al.
Abstract: The poloidal width of the filaments induced by the type-I edge localized mode has power dependence in EAST. The poloidal widths of the filaments observed by the high-speed vacuum ultraviolet (VUV) imaging system are proportional to the heating power and the ELM size. To understand this power dependence, the BOUT++ nonlinear simulations have been performed with the reconstructed equilibriums from the experimental measurements in this paper. The synthetic filament structures from BOUT++ nonlinear simulation match the experimental observations by the VUV imaging system. The BOUT++ nonlinear simulations also reproduce the power dependence of the filament widths and the ELM size. The filament width and the ELM size are inversely proportional to the toroidal mode number. The low- n mode has a broader radial and poloidal structure, which causes the larger filament width and ELM size. In the high input power case, the mode spectrum shifts to low- n, a result of increasing peeling drive. Besides, we found the β p in a higher input power case leads to a broader pedestal, expanding the radial mode structure of the peeling-ballooning mode.